Perbedaan Perilaku Bullying Di Tinjau Dari Jenis Kelamin - Fatmawati, Lili, Dra. Zahrotul Uyun, M. Si, Psi (2016)
Bullying is an act of hurting others who are weaker, both physically hurt, words, or feelings. Bullying has agreat opportunity to be imitated because of this negative behavior is mostly done by students. Bullying behavior is not only done by male students but also do by female students. The purpose of this study was to determine differences in bullying behavior in terms of gender. The hypothesis that there are differences in bullying behavior between male and female students. Subjects in this study amounted to 151 people who are students in grade VIII nd IX SMP Muhammadiyah 4 Surakarta. The sampling technique used in this research is the cluster random sampling. Methods of data collection approach with bullying behavior scale. Data analysis is done by sample t-test analysis using SPSS 1,742, significance (p) of 0, 084 (p>0,05) which means there is no difference in bullying behavior tendency between male and female.